Formation of the concept of the draft law "On building a circular economy" - Ilmeneva, Veronika Arturovna (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
Introduction. Involvement of waste in a circular economy requires independent legal regulation. At the same time, the linear economy is losing its relevance due to the development of a circular economy, therefore it is necessary to develop the legal basis for the circular economy. Empirical analysis. Legal regulation of the circular economy can be formalized as an independent normative legal act, which is preceded by a number of prerequisites, namely: an ambiguous concept of production and consumption waste, the absence of a number of criteria for determining a by-product, a secondary resource and waste, which characterizes the norms as conflicting. Conflicts are found not only in the formed legislation, but also in the latest amendments, which describes the actions of the legislator as inconsistent. The presence of the Federal classificaction catalogue is misleading in determining the properties of a substance and its classification as waste or a by-product of production. As follows from the strategic planning documents, the involvement of waste in the circular economy is planned on the basis of waste disposal, which is not a correct prerequisite. To form independent regulation of the circular economy, it is necessary to formulate the subject of regulation. Theoretical analysis. The proposed approach is to regulate the reduction of resource use and/or pollution at the source of their formation. For the practical implementation of the circular economy, the possibility of legal regulation of industrial symbiosis can be considered. One of the effects achieved with industrial symbiosis is an increase in production efficiency, which is one of the goals of the circular economy. It is also noted that there are no criteria for distinguishing waste from a by-product, with the presence or absence of useful properties being a possible criterion, which leads to imperfections in legal regulation. Results. It is proposed to change the regulation for the use of by-products of production, to establish independent regulation of the handling of secondary resources, and leave the regulation of only the handling of production and consumption waste in Federal Law 89-FZ.